Arsenic toxicity amelioration in rice soils by plant beneficial microbes - Mohapatra, Balaram; Bose, Himadri; Saha, Anumeha; Sar, Pinaki (ORYZA-An International Journal of Rice, 2020)
Over 50 million people are affected by groundwater arsenic (As) contamination beyond the prescribed safe limit of 10 μg/L across various regions in the Ganga-Brahmaputra basin of India. Among all, south-eastern Asiatic countries especially India and Bangladesh are most severely affected. Rice is the staple food for millions of people of this region and among many other crops, rice grains are champion in accumulating very high As. Irrigation of As-contaminated groundwater for rice cultivation has resulted in high deposition of As in topsoil and uptake in rice grain posing a serious threat to the sustainable agriculture. In addition, cooking and parboiling with As-contaminated water increases the As burden through dietary intake along with processed food items. Studies have shown that various factors like As solubility, bioavailability, microbial colonization, and uptake in the rice rhizosphere decides the fate of As transportation in rice. In this context, the use of plant growth promoting (PGP) microbial community members having both plant beneficial properties (increased production of phytohormone, enzymes, Siderophore, N2 fixation, P solubilization, disease resistance, mineral solubilization, etc.) and As amelioration or detoxification activities (biosorption, accumulation, volatilization, enhanced adsorption) can be a suitable alternative for sustainable rice farming in As-hotspots.